Prospect Analysis of Onion (allium cepa L) Production in Indonesia - Tori, Hadrianus; Dyanasari; Kholil, A. Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to analyze the production of shallots in Indonesia in the last 30 years to the next 30 years, and to analyze why the production of shallots in Indonesia cannot reach production levels as in China, India, the United States and Egypt. The secondary data used is time series data, namely the production of shallots in the last 30 years (1991-2020) using the trend analysis method, shallot production data for the period 1991 – 2020 will be used to predict shallot production for the next 30 years, namely 2021 -2050. The results, Indonesia shallot production in 2021 is 2,615,677, in 2050 it is 4,189,324. But in 2020 Indonesia imported shallots from Vietnam, Malaysia, Thailand of 8.17 thousand tonnes of production in 2020 of 1,815,445. For this reason, the government provides subsidized assistance in 2020 so that production increases by 20%, and production in 2021 increases by 3,138,812, production in 2050 is 5,027,189, if the government always provides subsidies, then Indonesia shallot production in the future will no longer be necessary. Imports in other words, Indonesia achieved self-sufficiency in shallots.